Analysis and implementation of wide zero‐voltage switching dual full‐bridge converters. Issue 4 (1st March 2016) - Lin, Bor‐Ren
Abstract : A new full‐bridge converter is presented to have the advantages of low conduction loss and wide zero‐voltage switching (ZVS) range. The proposed converter includes two dc–dc converters connected in parallel to reduce the current stresses of power components. Each dc–dc converter integrates a phase‐shift pulse‐width modulation full‐bridge circuit and an un‐regulated half‐bridge circuit sharing the lagging‐leg switches in order to reduce the switch counts. The un‐regulated half‐bridge circuit is adopted to extend the ZVS range of the lagging‐leg switches to improve the drawback of the narrow ZVS range in conventional full‐bridge converter. Two dc–dc converters share the lagging‐leg switches so that the switch counts in the proposed converter are less than the switches in conventional parallel full‐bridge converters. The resonant capacitors are used on the primary side of full‐bridge converters to reduce the primary current to zero at the freewheeling state. The secondary windings of full‐bridge and half‐bridge converters are connected in series to generate two positive voltage levels at the secondary rectified voltage. Therefore, the output inductor voltage at the freewheeling state is decreased and the output inductor size is reduced. Finally, the effectiveness of the proposed converter is verified by the experiments.